2019
DOI: 10.3233/jad-181123
|View full text |Cite
|
Sign up to set email alerts
|

Combined Transcriptomics and Proteomics in Frontal Cortex Area 8 in Frontotemporal Lobar Degeneration Linked to C9ORF72 Expansion

Abstract: Background: Frontotemporal lobar degeneration with TDP-43 immunoreactive inclusions (FTLD-TDP) may appear as sporadic (sFTLD-TDP) or linked to mutations in various genes including expansions of the non-coding region of C9ORF72 (c9FTLD). Objective: Analysis of differential mRNA and protein expression in the frontal cortex in c9FLTD and evaluation with previous observations in frontal cortex in sFTLD-TDP and amyotrophic lateral sclerosis with TDP-43 inclusions. Methods: Microarray hybridization and mass spectrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 86 publications
0
18
0
Order By: Relevance
“…The aim of our study was to identify cerebrospinal fluid (CSF) protein biomarkers that can differentiate between C9-ALS and C9-FTD cases and thus provide insight into the segregating clinical presentations. Until now, proteomic studies of patients with C9-ALS and C9-FTD have focused mainly on frontal cortex brain autopsy material 10 11. We decided to focus on CSF because sampling is usually done at the time of diagnosis and thus early proteomic changes can be detected.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of our study was to identify cerebrospinal fluid (CSF) protein biomarkers that can differentiate between C9-ALS and C9-FTD cases and thus provide insight into the segregating clinical presentations. Until now, proteomic studies of patients with C9-ALS and C9-FTD have focused mainly on frontal cortex brain autopsy material 10 11. We decided to focus on CSF because sampling is usually done at the time of diagnosis and thus early proteomic changes can be detected.…”
Section: Introductionmentioning
confidence: 99%
“…Aly/REF mediates mRNA export by interacting with the nuclear RNA export factor 1 (NXF1) and nuclear transport factor 2 (NTF2) related export protein 1 (NXT1) heterodimer [ 57 , 58 ]. Because mRNA processing is disrupted in C9ORF72 ALS/FTD [ 59 , 60 , 61 , 62 ], we explored this pathway as well as protein export by generating the mRNA export biosensor—NCT-A ( Figure 1 A and Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Andrés-Benito et al specifically analyzed the frontal cortex of 19 C9orf72 expansion-positive FTLD cases compared to 14 controls, combined with transcriptomics [ 39 ]. The biological functions of the 130 deregulated proteins were assessed using Ingenuity Pathway Analysis (IPA) software, which revealed abnormal expression of proteins in FTLD involved in inflammation (e.g., MSN, OPTN), along with several other deregulated pathways related to apoptosis (e.g., PPT1, CTSD), mitochondria (e.g., SOD2), and endocytosis (e.g., ANXA1/5, RAB7A, CLTC).…”
Section: Proteomic Studies In Ftld-tdpmentioning
confidence: 99%
“…Furthermore, the multifunctional kinase TBK1 and some of its downstream targets (e.g., OPTN ), in which loss-of-function mutations were described in FTD-ALS, exert important functions in inflammatory signaling [ 78 , 79 ]. Of interest, Andrés-Benito, et al found downregulation of OPTN in the frontal cortex of C9orf72 cases, disclosing broader involvement of this protein in FTLD-TDP [ 39 ].…”
Section: Converging Molecular Pathways In Ftld-tdpmentioning
confidence: 99%
See 1 more Smart Citation